2023
DOI: 10.1002/adfm.202300811
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Photo‐Degradation Study of α‐FAPbI3‐Based Perovskite Using In Situ X‐Ray Diffraction

Abstract: Hybrid halide perovskite has established its credibility as high performance thin film photovoltaic technology. Perovskite based on formamidinium cation is at the core composition to top performances and stability. Herein, a depth study based on temperature‐controlled in situ X‐ray diffraction focusing on the photo‐active formamidinium lead iodide (α‐FAPbI3) is reported. In particular, the thermal stability of the latter and the degradation pathways under different experimental conditions are clarified. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…A wide-bandgap Pb perovskite of composition FA 0.85 MA 0.15 Pb­(I 0.85 Br 0.15 ) 3 doped with the 5% potassium ion was fabricated for the top cell. FAPbI 3 has been applied to high-efficiency PSCs due to its superior characteristics such as an optimal bandgap, a longer diffusion length, and a high thermal stability. , Furthermore, the addition of MABr to FAPbI 3 is effective to suppress the transformation of α-phase to δ-phase at room temperature, which is unfavorable for efficient PSCs. The reason why the 5% potassium ion was doped into FA 0.85 MA 0.15 Pb­(I 0.85 Br 0.15 ) 3 is the reduction of the hysteresis of PSC, according to the previous report from Tang et al A Sn–Pb perovskite of composition Cs 0.025 FA 0.475 MA 0.5 Sn 0.5 Pb 0.5 I 3 with a narrow bandgap that works with a high PCE was chosen for the bottom cell . The detailed fabrication process of each perovskite film is given in the Experimental Methods, and the top-view scanning electron micrographs of the perovskite films are shown in Figure S1.…”
Section: Introductionmentioning
confidence: 99%
“…A wide-bandgap Pb perovskite of composition FA 0.85 MA 0.15 Pb­(I 0.85 Br 0.15 ) 3 doped with the 5% potassium ion was fabricated for the top cell. FAPbI 3 has been applied to high-efficiency PSCs due to its superior characteristics such as an optimal bandgap, a longer diffusion length, and a high thermal stability. , Furthermore, the addition of MABr to FAPbI 3 is effective to suppress the transformation of α-phase to δ-phase at room temperature, which is unfavorable for efficient PSCs. The reason why the 5% potassium ion was doped into FA 0.85 MA 0.15 Pb­(I 0.85 Br 0.15 ) 3 is the reduction of the hysteresis of PSC, according to the previous report from Tang et al A Sn–Pb perovskite of composition Cs 0.025 FA 0.475 MA 0.5 Sn 0.5 Pb 0.5 I 3 with a narrow bandgap that works with a high PCE was chosen for the bottom cell . The detailed fabrication process of each perovskite film is given in the Experimental Methods, and the top-view scanning electron micrographs of the perovskite films are shown in Figure S1.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that MAPbI 3 has a low decomposition temperature (∼60 °C) . Thus, prolonged exposure to thermal stress will likely lead to the gradual decomposition of the MA components in FA 0.6 MA 0.4 PbI 3 . In addition, it was observed that unencapsulated SC-PSCs exhibit a tendency to delaminate from extended exposure to thermal stress at 85 °C .…”
mentioning
confidence: 99%